1976
DOI: 10.1126/science.1273591
|View full text |Cite
|
Sign up to set email alerts
|

Residual Learning Deficit After Heavy Exposure to Cannabis or Alcohol in Rats

Abstract: Acute oral administration of cannabis extract to rats (tetrahydrocannabinol dose, 10 milligrams per kilogram) impaired maze learning. The impairment was more marked after ten daily doses of the same size. After 1, 2, or 3 months' pretreatment with the same daily dose, followed by a 25-day drug-free period, no residual learning impairment was found. However, 6 months of daily administration of cannabis (tetrahydrocannabinol, 20 milligrams per kilogram) or alcohol (6 grams per kilogram) produced significant resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
32
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 15 publications
5
32
0
Order By: Relevance
“…At least one month after drug discontinuation, animals were trained and tested on learning tasks. Compared to placebo-treated control rats, marijuana-treated rats demonstrated impairments on maze learning [63,64] and a differential reinforcement of lowrate responding task [65], and facilitated active avoidance learning on a shuttle-box task [66]. The authors note that these results are similar to findings among rats with hippocampal lesions [66], and suggest learning dysfunction associated with chronic marijuana administration.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…At least one month after drug discontinuation, animals were trained and tested on learning tasks. Compared to placebo-treated control rats, marijuana-treated rats demonstrated impairments on maze learning [63,64] and a differential reinforcement of lowrate responding task [65], and facilitated active avoidance learning on a shuttle-box task [66]. The authors note that these results are similar to findings among rats with hippocampal lesions [66], and suggest learning dysfunction associated with chronic marijuana administration.…”
supporting
confidence: 77%
“…Together, these results indicate a greater vulnerability to learning impairments when chronic marijuana exposure occurs during adolescence, and limited cognitive dysfunction when marijuana exposure occurs among mature animals [67]. Further, lighter THC doses of 10 mg/kg did not produce significant learning impairments [63], suggesting that only heavy marijuana use is associated with learning deficits in adolescents.More recently, prepulse inhibition, object recognition, and motivation were examined among rats that had received chronic treatment with the synthetic cannabinoid agonist WIN 55,212-2 either as adolescents or adults [68]. Adolescent treatment began at 40 days of age, while adult treatment began at 70 days.…”
mentioning
confidence: 74%
“…With regard to the last of these cannabis use has been shown to adversely affect the maintenance of attention, short term memory and executive functions (Hall & Solowij, 1998; Pope & YurgelunTodd, 1996;Pope et al 2001). Animal studies have revealed that chronic administration of the cannabinoid THC causes hippocampal damage and impairs maze learning in rats (Fehr et al, 1976;Lawston et al 2000).…”
Section: Edge Hill College Of Higher Educationmentioning
confidence: 99%
“…With regard to the last of these cannabis use has been shown to adversely affect the maintenance of attention, short term memory and executive functions (Hall & Solowij, 1998; Pope & YurgelunTodd, 1996;Pope et al 2001). Animal studies have revealed that chronic administration of the cannabinoid THC causes hippocampal damage and impairs maze learning in rats (Fehr et al, 1976;Lawston et al 2000).However, the anti-inflammatory and anti-oxidative properties of cannabinoids have also raised the possibility that they may have beneficial effects in limiting neurological damage (Carter et al 2004;Grundy, 2002). For example, the inhibitory effects of cannabinoids on the excitotoxic neurotransmitter glutamate (Drysdale & Platt, 2003) and their capacity to counter the oxidative damage to dopaminergic neurones has raised the possibility that they may be of value in the treatment of At the neuronal level low doses of cannabinoids can elevate intracellular calcium levels and increase transmitter release (Sarne & Keren, 2004).…”
mentioning
confidence: 99%
“…The psychoactive properties of cannabis are mainly due to one of these cannabinoids, Δ 9 tetrahydrocannabinol, (THC). Animal studies have revealed that chronic administration of THC causes hippocampal damage and impairs maze learning in rats (Fehr et al, 1976;Lawston et al, 2000). In humans, cannabinoids may be neurotoxic or neuroprotective depending on their concentration, the timing of delivery and the cell type (Doble, 1999;Guzman et al, 2001;Hubert & Doble, 1998).…”
mentioning
confidence: 99%